PENGUKURAN KINERJA PERUSAHAAN DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD (Studi Kasus pada CV. Roda Mas Jaya Semarang) - Indra Novanditya; Hari Susanta Nugraha; Wahyu Hidayat (Universitas Diponegoro, 2013)
Balanced scorecard has a privilege in terms of coverage measurement is a fairly comprehensive because while taking into consideration the financial performance, balanced scorcard also consider the performance of non-financial performance, namely customer, internal business processes, and learning and growth. Referring to the problems faced by CV. Roda Mas Jaya Semarang, this research examines: